Environmental Strategy, Environmental Management Accounting and Organizational Performance: Evidence from The United Arab Emirates Market - Al-Mawali, Hamzah; Sharif, Ahmed Al; Rumman, Ghaleb Abu; Kerzan, Faten (Journal of Environmental Accounting and Management, 2026)
The purpose of this paper is to examine the association between the Environmental Strategy (ES) and Environmental Management Accounting (EMA) usage. It also aims to consider the effect of EMA usage on the organizational performance. A research framework was developed based on the contingency theory. Data were collected via questionnaires distributed to companies listed on UAE Stock Markets (ADX and DFM) in 2016. Data were analyzed using a structural equation modelling. The model was statistically validated and evaluated. The results indicated that ES positively affects the level of EMA usage and a positive relationship between EMA and the organizational performance. These findings contribute to the management accounting contingency-based research by providing empirical evidence to support that relationship between ES and EMA as well as between EMA and the organizational performance in the context of developing countries.